2023
DOI: 10.1038/s41562-023-01764-w
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ looking preferences for social versus non-social objects reflect genetic variation

Ana Maria Portugal,
Charlotte Viktorsson,
Mark J. Taylor
et al.

Abstract: To what extent do individual differences in infants’ early preference for faces versus non-facial objects reflect genetic and environmental factors? Here in a sample of 536 5-month-old same-sex twins, we assessed attention to faces using eye tracking in two ways: initial orienting to faces at the start of the trial (thought to reflect subcortical processing) and sustained face preference throughout the trial (thought to reflect emerging attention control). Twin model fitting suggested an influence of genetic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Atypical gaze patterns have long been studied in autism 13,20,21 and may represent a key example of how genetic starting points linked to autism affect brain development in ways to create atypical niche construction via how individuals sample the world around them from very early points in development [22][23][24][25][26] . Both individualsensitive gaze patterns and autistic traits are likely phenotypes sensitive to heritable polygenic or omnigenic common genetic architecture [13][14][15]49,51 and support the idea that gaze fingerprinting metrics may be a genetically sensitive signal that can predict variation in autistic traits. Here we find evidence supporting the utility of gaze fingerprinting metrics as predictive of variation in autistic traits such that higher gaze fingerprintability is linked to lower levels of autistic traits.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Atypical gaze patterns have long been studied in autism 13,20,21 and may represent a key example of how genetic starting points linked to autism affect brain development in ways to create atypical niche construction via how individuals sample the world around them from very early points in development [22][23][24][25][26] . Both individualsensitive gaze patterns and autistic traits are likely phenotypes sensitive to heritable polygenic or omnigenic common genetic architecture [13][14][15]49,51 and support the idea that gaze fingerprinting metrics may be a genetically sensitive signal that can predict variation in autistic traits. Here we find evidence supporting the utility of gaze fingerprinting metrics as predictive of variation in autistic traits such that higher gaze fingerprintability is linked to lower levels of autistic traits.…”
Section: Discussionmentioning
confidence: 52%
“…However, because gaze patterns can also be quite stable and systematic [6][7][8][9][10][11][12] , this suggests that there must also be a strong within-individual factor that explains variance in gaze patterns. Recent twin studies have revealed heritable common genetic variation to be one such powerful within-individual mechanism constraining gaze patterns [13][14][15] . These insights suggest the possibility that gaze patterns may be an important individuating signature or 'fingerprint' of high neurobiological and developmental significance.…”
mentioning
confidence: 99%
“…One longitudinal study found that reduced face preference at 5 weeks of age predicted callous-unemotional traits at 2.5 years (Bedford et al, 2015), suggesting that, already very early in life, attention to social stimuli is important for later development. Another study of infant twins found that face preference at 5 months was heritable and linked specifically to verbal competence at 14 months (Portugal et al, 2023). The same specificity has been found for the tendency to look at either the eyes or the mouth, another social attention phenotype that has been found to be highly heritable in both toddlerhood (Constantino et al, 2017) and infancy (Viktorsson et al, 2023).…”
Section: Introductionmentioning
confidence: 71%